The figure of the Dandy in Barbey d'Aurevilly's "Le bonheur dans le crime" - Eisenberg, Davina L. (Sexuality and literature, 1996)
This study examines the figure of the dandy in Barbey d'Aurevilly's short-story, "Le bonheur dans le crime", one of 6 Diaboliques (1874), in an attempt to bridge a gap in aurevillian criticism. This short story is a piece of dandy-writing, in that it takes up several significant issues Barbey had raised in his essay on dandyism of 1845, "Du Dandysme et de George Brummell": dress, sexuality and the notion of the mask